The Teachers’ Perception of Using Peer Editing Technique in Writing at SMP An Namiroh Pekanbaru - Harni, Meylida; Syafi'i S, M. (Journal of English and Arabic Language Teaching, 2024)
Perception is a process where the teacher observes something and reacts to it based on facts that are what the teacher sees and fells. Meanwhile, writing is a way to convey ideas, thoughts, and opinion that are in our minds. And peer editing is a technique used to determined abilities, especially in writing. With the teacher’s perception regarding the use of peer editing techniques in writing, the teacher can evaluate the use of this technique and whether this technique is effective in improving  students’ writing abilities. This research aim to find teachers’ opinion regarding the use of peer editing technique in writing at SMP An Namiroh Pekanbaru. This research is qualitative research. This research was conducted in August 2023 at SMP An Namiroh Pekanbaru. The population of this research were English teachers at SMP AN-NAmiroh Pekanbaru who has experience in teaching English. The data collection technique in this reseach used interviews, and two teachers were interviewed. Then the information obtained from the teacher is explained and concluded. The finding obtained show that all English teachers have positive opinion regarding the use of this technique even though there are several obstacles experienced when implementing it. This technique is very useful for improving students’ writing abilities.